Implementation Of Digital Technology As An Effort To Create Differentiated Learning In Achieving IKM (Independent Curriculum Implementation) In Schools: Implementation Of Digital Technology As An Effort To Create Differentiated Learning In Achieving IKM (Independent Curriculum Implementation) In Schools - Riska Imanda; Sri Setiawaty; Fakhrah Fakhrah; Karismayani Karismayani; Wandira Kinanti (LPPM Universitas Malikussaleh, 2024)
Abstract. The basic principle of integrating digital media (technology) in learning aims to improve students' conceptual understanding and develop students' ability to communicate in carrying out their roles both in the world of education and in society. This research aims to determine the effect of implementing digital technology to create differentiated learning in achieving IKM (Independent Curriculum Implementation) in schools, focusing on students' critical thinking abilities. The technique for determining school research locations uses random sampling techniques. The research used a quasi-experiment with a non-equivalent control group research design, where the experimental class was treated with the implementation of digital media using the Read, Answer, Discussion, Explain, and Create (RADEC) model. In contrast, the control class used an expository learning model. Tests to measure students' critical thinking competencies are given in the form of pretest and posttest. The results of students' critical thinking results showed that the average pretest scores for the experimental and control classes were 28.18 and 25.76, while the posttests for the experimental and control classes were 84.47 and 69.92. This shows that after being given treatment there was an improvement compared to before being given treatment. Test the Critical Thinking hypothesis using the Maan-Whitney test, if the Asymp Sig value is < 0.05, then the Hypothesis is accepted, and if the Asymp Sig value is > 0.05 then the Hypothesis is rejected. It can be concluded that there is an influence of the implementation of digital technology on students' critical thinking abilities using the Read, Answer, Discussion, Explain, and Create (RADEC) model.